The use of referential cohesion in academic texts by Persian EFL learners - Sahar Naderi,; Yuen, Chee Keong; Hafizah Latif, (Penerbit UKM, 2013)
Writing cohesively remains a challenging task for many ESL and EFL learners and users of English, even at advanced levels. Despite its importance in academic writing, elements of cohesion have rarely been researched especially among Persian EFL writers. This study is aimed at filling the gap in the literature through an investigation of referential ties as one of the most explicit cohesion markers (Halliday and Matthiessen 2004). Papers by Persian scholars in the engineering field who attended a Nanotech conference in Malaysia, were reviewed for referential ties based on Systemic Functional Grammar (Halliday 1994; Halliday and Matthiessen 2004). The distribution and categorization of such ties were described using both descriptive and inferential statistics. Subsequently the reference usage by Persians who performed research in Malaysian and Iranian universities were compared. A discussion is presented to examine any improvements due to the environment for the group of Persians studying in Malaysian universities using English language as the medium of instruction. The results confirm that Persians studying in Malaysian universities produce and repeat some components of referential ties more frequently in their academic writing when compared with their peers studying in Iranian universities. In addition, the results of this study are compared with the findings of some other studies among ESL/EFL learners of different nationalities to explain the cases of overuse, underuse, and misuse of referential cohesion which has implications for pedagogical objectives.